Family Politics and Deception in Northern North America and West-Central Africa : Litigating Gods Marriage Intention? - Fossungu, Peter Ateh-Afac (Book collections on Project MUSE., 2015)
Largely concerned with Family Politics and Deception in northern North America and West-Central Africa, this book is intended mostly to provoke and enlighten. The book fossungupalogizes on whether or not northern North American courts are able to live up to the standard of 'exclusively saying exactly what the law is' in regard of the apparent war between the mounting same-sex marriage legalization drive and the traditional Western religious conception of marriage as endorsed by America's 1996 Defense of Marriage Act. It also tackles some intriguingly troubling matters emanating from African customary marriages and inheritance, subjects presenting some odd faces of marriage and family very similar at times to those engendered by same-sex marriage in northern North America. Its underlying preaching is that positive things could often be found even in tragedies. Hence, you should learn to make the best of your troubles instead of letting these haunt you - a goal easily attained by cultivating the habit of looking at the larger picture of things. Even one's "stupid" and non-professional ideas could be learning ground to more people than one ever could have imagined.